Word Order in Adjective-Noun Pairs Inside and Outside the Prepositional Phrase: A Contribution to the 15th International Congress of Slavists (Minsk, 2013) - Minlos, Philip R. (Slověne, 2012)
This paper discusses a statistical correlation between possessive prenominal placement and the presence of a preposition. The data from mediaeval Russian, Czech, and Croatian are validated against standard statistical measures (chisquare (X2) test and phi (φ) coefficient). Different explanations for the correlation are proposed; the most natural and simple one links the syntactic feature with the phonetic chunking of preposition and adjacent possessive, strengthened by their frequent co-occurence.